2017
DOI: 10.1177/0190272517706048
|View full text |Cite
|
Sign up to set email alerts
|

I-Challenges: Influencing Others’ Perspectives by Mentioning Personal Experiences in Therapeutic Community Group Meetings

Abstract: In this article, I examine the communicative practice of mentioning a personal experience as a vehicle for challenging a peer's perspective. I study this in the context of therapeutic community (TC) group meetings for clients recovering from drug misuse. Using conversation analysis, I demonstrate that TC clients use this practice, which I call an I-challenge, to influence how their peers make sense of their own experiences and to do so without commenting on those peers' experiences and perspectives. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…In responding to self-disclosures, speakers utilize a repertoire of means to display how they have come to know something, whether through evidencing their own experience by revealing private details or through resorting to claiming something as general knowledge. As pointed out by Pino (2017), challenging a peer's perspective is a delicate process, and making claims that are based on the speaker's own experiences is an effective way to challenge the other while maintaining a relationship with them.…”
Section: Discussionmentioning
confidence: 99%
“…In responding to self-disclosures, speakers utilize a repertoire of means to display how they have come to know something, whether through evidencing their own experience by revealing private details or through resorting to claiming something as general knowledge. As pointed out by Pino (2017), challenging a peer's perspective is a delicate process, and making claims that are based on the speaker's own experiences is an effective way to challenge the other while maintaining a relationship with them.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in this paper, we argue that we still know very little about actual manifestations of persuasive conduct 'in the wild'. Taking a discursive psychological approach to the study of people in the settings that comprise their everyday lives, we respecify persuasion as a visible, situated, and interactive accomplishment, rather than starting from a conceptualisation of it as an outcome of invisible cognitive processes (Humă, Stokoe, & Sikveland, 2019;Pino, 2017;Wooffitt, 2005).…”
Section: Putting Persuasion (Back) In Its Interactional Contextmentioning
confidence: 99%
“…For example, ethnomethodological research building on Garfinkel's (1967) pioneering analysis of the situated accomplishment of gender has presented a reconceptualization of asymmetries based on gender, race, and class as ongoing interactional accomplishments rather than merely ascribed or quantitatively measured attributes (West & Fenstermaker, 1995;West & Zimmerman, 1987). Moreover, conversation analytic studies based on Schegloff's (1997) principles have demonstrated how participants in interactions can use gender, race, and class categories (Stokoe, 2009;Whitehead, 2012Whitehead, , 2013, as well as "individual-level" attributes such as previous life experiences (Pino, 2017), as resources for producing actions and interpreting the actions of others. However, to our knowledge, no research has used ethnomethodological and conversation analytic methods to examine how factors such as these are produced or oriented to by participants specifically in interactions in which violence either occurs or is projected (by the participants) as a potential outcome.…”
Section: Situation-sensitive Approachesmentioning
confidence: 99%